Semiotic analysis of delusion - V. E. Pashkovskiy (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Delusion is the most difficult problem in psychopathology. In the existing definitions of delusion there is no clear indication of the discriminant that enables us to reliably distinguish it from other psychopathologic phenomena. This paper proposes an approach to examine delusion as semiotic object that has a symbolic nature. The paper accentuates that a person, along with the biological means of processing and storage of information uses natural and artificial sign systems. Self reflection in our consciousness of objective reality is also an information process with sign-symbolic structure. Therefore, the use of ideas and methods of modern semiotics becomes the conceptual framework that can expand our understanding of the psychopathology of delusion. Destruction of semiosis, ie, the process of generating value, apparently is that discriminant, which allows us to distinguish delusion from other similar phenomena, for example, from overvalued ideas.